Method for improving high-temperature mechanical property of molybdenum single crystal and maintaining structural stability of single crystal
The method addresses the challenge of maintaining the single crystal structure of molybdenum single crystals by using a powder metallurgy process with controlled niobium composition and electron beam zone melting, enhancing mechanical properties and facilitating efficient structural analysis.
Patent Information
- Application Number
- CN202411306729.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
Existing methods for processing molybdenum single crystals face challenges in maintaining the single crystal structure during high-temperature deformation, leading to recrystallization and poor mechanical properties.
A method involving powder metallurgy to prepare a molybdenum-niobium alloy sintered bar, followed by smelting, extrusion, forging, and machining, and electron beam zone melting to produce a molybdenum-niobium alloy single crystal rod, with controlled niobium composition to enhance mechanical properties and maintain the single crystal structure.
The method improves the high-temperature mechanical properties of molybdenum single crystals by inhibiting recrystallization, maintaining the single crystal structure, and provides a fast and intuitive analysis using electron backscatter diffraction.
Smart Images

Figure CN119194610A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of refractory metal material processing, and specifically relates to a method for improving the high-temperature mechanical properties of a molybdenum single crystal and maintaining the stability of the single crystal structure. Background Art
[0002] Molybdenum single crystals are currently used as key high-temperature structural materials for advanced nuclear reactors. Mechanical properties and single crystal structural stability are key performance indicators to ensure the safe operation of components. Generally, the recrystallization behavior of single crystals during plastic deformation is a key obstacle to single crystal processing. How to deform the material to obtain a good strength-plasticity match while ensuring the single crystal structure is the key problem currently faced in improving the processing performance of molybdenum alloy single crystals. The traditional hot working methods will cause molybdenum single crystals to recrystallize, making it difficult to maintain the single crystal structure after hot deformation.
[0003] Therefore, there is an urgent need for a method to improve the high-temperature mechanical properties of molybdenum single crystals and maintain the stability of the single crystal structure. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for improving the high-temperature mechanical properties of molybdenum single crystals and maintaining the stability of single crystal structures in view of the deficiencies of the above-mentioned prior art. The method adopts a powder metallurgy method to preliminarily prepare a molybdenum-niobium alloy sintered bar, and then further obtains a molybdenum-niobium alloy raw material rod through smelting, extrusion, forging and machining, and then electron beam zone melting is performed to obtain a molybdenum-niobium alloy single crystal rod. By controlling the composition, it is ensured that the alloyed molybdenum-niobium alloy single crystal can both improve the mechanical properties of the molybdenum single crystal and maintain the single crystal structure. Finally, the molybdenum-niobium alloy single crystal rod is analyzed, and a high-temperature mechanical property test is first performed, and then the sample after the high-temperature mechanical property test is analyzed, which proves that the mechanical properties of the molybdenum single crystal are improved, and the single crystal structure destruction caused by dynamic recrystallization during thermal deformation is avoided.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for improving the high temperature mechanical properties of molybdenum single crystal and maintaining the stability of the single crystal structure, characterized in that the method comprises the following steps:
[0006] Step 1: preparing a molybdenum-niobium alloy sintered bar by powder metallurgy;
[0007] Step 2: melting, extruding, forging and machining the molybdenum-niobium alloy sintered bar prepared in step 1 in sequence to obtain a molybdenum-niobium alloy raw material bar;
[0008] Step 3: Electron beam zone melting the molybdenum-niobium alloy raw material rod obtained in step 2 to obtain a molybdenum-niobium alloy single crystal rod;
[0009] Step 4: Prepare the molybdenum-niobium alloy single crystal rod obtained in step 3 as a sample, and then conduct high-temperature mechanical property test and structural analysis in sequence to determine its high-temperature mechanical properties and single crystal structural stability.
[0010] The present invention adopts a powder metallurgy method to preliminarily prepare a molybdenum-niobium alloy sintered bar, and then obtains a molybdenum-niobium alloy raw material rod through smelting, extrusion, forging and machining, and then performs electron beam zone melting to obtain a molybdenum-niobium alloy single crystal rod. By controlling the composition, it is ensured that the molybdenum-niobium alloy single crystal after alloying can both improve the mechanical properties of the molybdenum single crystal and maintain the single crystal structure. Finally, the molybdenum-niobium alloy single crystal rod is analyzed, and a high-temperature mechanical property test is first performed, and then the sample after the high-temperature mechanical property test is analyzed, which proves that the mechanical properties of the molybdenum single crystal are improved, and the single crystal structure destruction caused by dynamic recrystallization during thermal deformation is avoided.
[0011] The above method for improving the high temperature mechanical properties of molybdenum single crystal and maintaining the stability of the single crystal structure is characterized in that the melting in step 2 is electron beam suspension zone melting. The present invention improves the high temperature mechanical properties of molybdenum single crystal by using electron beam suspension zone melting.
[0012] The above-mentioned method for improving the high-temperature mechanical properties of molybdenum single crystals and maintaining the stability of the single crystal structure is characterized in that the mass percentage of niobium in the molybdenum-niobium alloy single crystal rod in step 4 is 3% to 6%, and the balance is molybdenum. The present invention improves the mechanical properties of the molybdenum single crystal to a large extent by controlling the mass percentage of the added niobium, and avoids the destruction of the single crystal structure caused by dynamic recrystallization during thermal deformation.
[0013] The above-mentioned method for improving the high-temperature mechanical properties of molybdenum single crystals and maintaining the stability of single crystal structures is characterized in that the preparation of the sample in step 4 is specifically: using wire cutting to cut a cylindrical compression sample with a diameter of 6 mm and a length of 9 mm from a molybdenum-niobium alloy single crystal rod. The present invention facilitates subsequent testing by controlling the process of preparing the sample.
[0014] The above-mentioned method for improving the high-temperature mechanical properties of molybdenum single crystals and maintaining the stability of the single crystal structure is characterized in that the equipment used for the high-temperature mechanical properties test in step 4 is a Gleeble-1500D thermal simulation tester, the temperature used for the high-temperature mechanical properties test is 1100°C to 1400°C, and the strain rate is 10 -2 s -1 The deformation is 50%. The invention accurately obtains the high temperature mechanical properties of the molybdenum-niobium alloy single crystal rod by controlling the parameters of the high temperature mechanical properties test.
[0015] The above-mentioned method for improving the high-temperature mechanical properties of molybdenum single crystals and maintaining the stability of single crystal structures is characterized in that the structural analysis in step 4 is single crystal structure analysis, specifically, the crystal orientation of the single crystal sample is determined by electron backscatter diffraction. The present invention uses electron backscatter diffraction to determine the crystal orientation of the single crystal sample, which is simple and convenient, shortens the operation time of single crystal determination, is fast and intuitive, and improves the determination efficiency.
[0016] Compared with the prior art, the present invention has the following advantages:
[0017] 1. The present invention adopts a powder metallurgy method to preliminarily prepare a molybdenum-niobium alloy sintered bar, and then further obtains a molybdenum-niobium alloy raw material rod through smelting, extrusion, forging and machining, and then performs electron beam zone melting to obtain a molybdenum-niobium alloy single crystal rod. By controlling the composition, it is ensured that the alloyed molybdenum-niobium alloy single crystal can both improve the mechanical properties of the molybdenum single crystal and maintain the single crystal structure. Finally, the molybdenum-niobium alloy single crystal rod is analyzed, and a high-temperature mechanical property test is first performed, and then the sample after the high-temperature mechanical property test is analyzed, which proves that the mechanical properties of the molybdenum single crystal are improved, and the single crystal structure destruction caused by dynamic recrystallization during thermal deformation is avoided.
[0018] 2. The present invention adopts an alloying method to add an appropriate amount of Nb, which greatly improves the mechanical properties of the molybdenum single crystal and avoids the destruction of the single crystal structure caused by dynamic recrystallization during thermal deformation.
[0019] 3. The molybdenum-niobium single crystal prepared by electron beam suspension zone melting in the present invention not only improves the high-temperature mechanical properties of the molybdenum single crystal after adding the Nb element, but the addition of the Nb element effectively inhibits the dislocation and subgrain boundary migration process, thereby allowing the molybdenum single crystal to maintain a single crystal structure during thermal deformation.
[0020] 4. The present invention uses EBSD to determine the crystal orientation of the single crystal sample after thermal deformation, which is simple and convenient, shortens the operation time of single crystal determination, is fast and intuitive, and improves the determination efficiency.
[0021] 5. The preparation method of the present invention is easy to operate and has universality, and provides a reference for the composition design of molybdenum alloy single crystals of other systems.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of crystal orientation of the molybdenum-niobium alloy single crystal rod obtained in Example 1 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1.
[0024] Figure 2This is a test diagram of high temperature compression performance of the molybdenum-niobium alloy single crystal rod obtained in Example 1 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1.
[0025] Figure 3 EBSD diagrams of the molybdenum-niobium alloy single crystal rod obtained in Example 1 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1 after high temperature mechanical property testing.
[0026] Figure 4 Schematic diagram of the crystal orientation of the molybdenum-niobium alloy single crystal rod obtained in Example 2 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1.
[0027] Figure 5 This is a test diagram of high temperature compression performance of the molybdenum-niobium alloy single crystal rod obtained in Example 2 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1.
[0028] Figure 6 EBSD diagrams of the molybdenum-niobium alloy single crystal rod obtained in Example 2 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1 after high temperature mechanical property testing. DETAILED DESCRIPTION
[0029] Example 1
[0030] This embodiment includes the following steps:
[0031] Step 1: preparing a molybdenum-niobium alloy sintered bar by powder metallurgy;
[0032] Step 2: melting, extruding, forging and machining the molybdenum-niobium alloy sintered bar prepared in step 1 in sequence to obtain a molybdenum-niobium alloy raw material bar;
[0033] Step 3: subjecting the molybdenum-niobium alloy raw material rod obtained in step 2 to electron beam suspension zone melting to obtain a molybdenum-niobium alloy single crystal rod;
[0034] Step 4: Place the molybdenum-niobium alloy single crystal rod obtained in step 3 along the axial direction. <111> The wire is fed in a direction to cut a cylindrical compression specimen with a diameter of 6 mm and a length of 9 mm from the molybdenum-niobium alloy single crystal rod by wire cutting, and then high-temperature mechanical property test and structural analysis are carried out in sequence to determine its high-temperature mechanical property and single crystal structural stability; the mass percentage of niobium in the molybdenum-niobium alloy single crystal rod is 3%, and the balance is molybdenum; the equipment used for the high-temperature mechanical property test is a Gleeble-1500D thermal simulation testing machine, and the temperatures used for the high-temperature mechanical property test are 1100°C, 1200°C, 1300°C, 1400°C, and the strain rate is 10 -2 s -1, the deformation amount is 50%; in the high-temperature mechanical properties test, the deformation temperature is reached at a heating rate of 10°C / s, and the sample is kept warm for 1 minute to ensure that the sample temperature is uniform. In order to reduce the friction between the sample surface and the fixture, a tantalum foil with a thickness of 0.1 mm is placed on the sample surface during compression. In the high-temperature mechanical properties test, when the deformation reaches the preset deformation amount, it is immediately water quenched, and the delay time does not exceed 3 seconds to retain the high-temperature structure of the deformed sample. Finally, the central area of the sample cross section after hot compression is selected for structural analysis; the structural analysis is a single crystal structural analysis, specifically, the electron backscatter diffraction method (EBSD) is used to determine the crystal orientation of the single crystal sample.
[0035] Comparative Example 1
[0036] This comparative example comprises the following steps:
[0037] Step 1: preparing molybdenum sintered bars by powder metallurgy;
[0038] Step 2: melting, extruding, forging and machining the molybdenum sintered bar prepared in step 1 in sequence to obtain a molybdenum raw material bar;
[0039] Step 3: subjecting the molybdenum raw material rod obtained in step 2 to electron beam suspension zone melting to obtain a molybdenum single crystal rod;
[0040] Step 4: Place the molybdenum single crystal rod obtained in step 3 along the axial direction. <111> The wire is fed in the direction of the wire cutting to cut out a cylindrical compression specimen with a diameter of 6 mm and a length of 9 mm on the molybdenum single crystal rod, and then high-temperature mechanical properties test and structural analysis are carried out in turn to determine its high-temperature mechanical properties and single crystal structural stability; the equipment used for the high-temperature mechanical properties test is a Gleeble-1500D thermal simulation testing machine, and the temperatures used for the high-temperature mechanical properties test are 1100°C, 1200°C, 1300°C, 1400°C, and the strain rate is 10 -2 s -1 , the deformation amount is 50%; in the high-temperature mechanical properties test, the deformation temperature is reached at a heating rate of 10°C / s, and the sample is kept warm for 1 minute to ensure that the sample temperature is uniform. In order to reduce the friction between the sample surface and the fixture, a tantalum foil with a thickness of 0.1 mm is placed on the sample surface during compression. In the high-temperature mechanical properties test, when the deformation reaches the preset deformation amount, it is immediately water quenched, and the delay time does not exceed 3s to retain the high-temperature structure of the deformed sample. Finally, the central area of the sample cross section after hot compression is selected for structural analysis; the structural analysis is a single crystal structure analysis, specifically, the electron backscatter diffraction method is used to determine the crystal orientation of the single crystal sample.
[0041] Figure 1Figure 1 is a schematic diagram of the crystal orientation of the molybdenum-niobium alloy single crystal rod obtained in Example 1 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1. a is a schematic diagram of the crystal orientation of the molybdenum single crystal rod obtained in Comparative Example 1, and b is a schematic diagram of the crystal orientation of the molybdenum-niobium alloy single crystal rod obtained in Example 1. The figure on the right is the reference color of the crystal orientation. If it is a single crystal, a and b are one color, and if it is a polycrystalline, a and b are multiple colors. Figure 1 It can be seen that the molybdenum-niobium alloy single crystal rod obtained in Example 1 and the molybdenum single crystal rod obtained in Comparative Example 1 are both <111> Oriented single crystal structure.
[0042] Figure 2 The figure is a high temperature compression performance test diagram of the molybdenum-niobium alloy single crystal rod obtained in Example 1 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1. The left side is a high temperature compression performance test diagram of the molybdenum single crystal rod obtained in Comparative Example 1, and the right side is a high temperature compression performance test diagram of the molybdenum-niobium alloy single crystal rod obtained in Example 1. Figure 2 It can be seen that the compressive strength of the molybdenum-niobium alloy single crystal rod obtained in Example 1 is higher than that of the molybdenum single crystal rod obtained in Comparative Example 1.
[0043] Figure 3 EBSD images of the molybdenum-niobium alloy single crystal rod obtained in Example 1 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1 after high-temperature mechanical properties testing, a is a schematic diagram of the crystal orientation of the molybdenum single crystal rod obtained in Comparative Example 1 after high-temperature mechanical properties testing, b is a schematic diagram of the crystal orientation of the molybdenum-niobium alloy single crystal rod obtained in Example 1 after high-temperature mechanical properties testing, and the right side of the figure is the reference color of the crystal orientation. If it is a single crystal, a and b are one color, and if it is a polycrystalline, a and b are multiple colors. Figure 3 It can be seen that the molybdenum single crystal rod obtained in Comparative Example 1 undergoes recrystallization after thermal deformation, while the molybdenum-niobium alloy single crystal rod obtained in Example 1 still maintains a single crystal structure after thermal deformation.
[0044] It was tested that the compressive strength of the molybdenum-niobium alloy single crystal rod obtained in Example 1 was 137.5 MPa, and the single crystal structure was maintained after thermal deformation, while the compressive strength of the molybdenum single crystal rod obtained in Comparative Example 1 was 102.8 MPa, and recrystallization occurred after thermal deformation.
[0045] Example 2
[0046] This embodiment includes the following steps:
[0047] Step 1: preparing a molybdenum-niobium alloy sintered bar by powder metallurgy;
[0048] Step 2: melting, extruding, forging and machining the molybdenum-niobium alloy sintered bar prepared in step 1 in sequence to obtain a molybdenum-niobium alloy raw material bar;
[0049] Step 3: subjecting the molybdenum-niobium alloy raw material rod obtained in step 2 to electron beam suspension zone melting to obtain a molybdenum-niobium alloy single crystal rod;
[0050] Step 4: Place the molybdenum-niobium alloy single crystal rod obtained in step 3 along the axial direction. <111> The wire is fed in a direction to cut a cylindrical compression specimen with a diameter of 6 mm and a length of 9 mm from the molybdenum-niobium alloy single crystal rod by wire cutting, and then a high-temperature mechanical property test and a structural analysis are carried out in sequence to determine the high-temperature mechanical property and the stability of the single crystal structure; the mass percentage of niobium in the molybdenum-niobium alloy single crystal rod is 6%, and the balance is molybdenum; the equipment used for the high-temperature mechanical property test is a Gleeble-1500D thermal simulation tester, and the temperatures used for the high-temperature mechanical property test are 1100°C, 1200°C, 1300°C, 1400°C, and the strain rate is 10 -2 s -1 , the deformation amount is 50%; in the high-temperature mechanical properties test, the deformation temperature is reached at a heating rate of 10°C / s, and the sample is kept warm for 1 minute to ensure that the sample temperature is uniform. In order to reduce the friction between the sample surface and the fixture, a tantalum foil with a thickness of 0.1 mm is placed on the sample surface during compression. In the high-temperature mechanical properties test, when the deformation reaches the preset deformation amount, it is immediately water quenched, and the delay time does not exceed 3 seconds to retain the high-temperature structure of the deformed sample. Finally, the central area of the sample cross section after hot compression is selected for structural analysis; the structural analysis is a single crystal structural analysis, specifically, the electron backscatter diffraction method (EBSD) is used to determine the crystal orientation of the single crystal sample.
[0051] Figure 4 Schematic diagrams of crystal orientation of the molybdenum-niobium alloy single crystal rod obtained in Example 2 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1, a is a schematic diagram of crystal orientation of the molybdenum single crystal rod obtained in Comparative Example 1, b is a schematic diagram of crystal orientation of the molybdenum-niobium alloy single crystal rod obtained in Example 2, and the right figure is a reference color for crystal orientation. If it is a single crystal, a and b are one color, and if it is a polycrystalline, a and b are multiple colors. Figure 4 It can be seen that both the molybdenum-niobium alloy single crystal rod and the molybdenum single crystal rod are <111> Oriented single crystal structure.
[0052] Figure 5 The figure is a high temperature compression performance test diagram of the molybdenum-niobium alloy single crystal rod obtained in Example 2 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1. The left side is a high temperature compression performance test diagram of the molybdenum single crystal rod obtained in Comparative Example 1, and the right side is a high temperature compression performance test diagram of the molybdenum-niobium alloy single crystal rod obtained in Example 2. Figure 5 It can be seen that the compressive strength of the molybdenum-niobium alloy single crystal rod obtained in Example 2 is higher than that of the molybdenum single crystal rod obtained in Comparative Example 1.
[0053] Figure 6 EBSD images of the molybdenum-niobium alloy single crystal rod obtained in Example 2 of the present invention and the molybdenum single crystal rod obtained in Comparative Example 1 after high-temperature mechanical properties testing, a is a schematic diagram of the crystal orientation of the molybdenum single crystal rod obtained in Comparative Example 1 after high-temperature mechanical properties testing, b is a schematic diagram of the crystal orientation of the molybdenum-niobium alloy single crystal rod obtained in Example 2 after high-temperature mechanical properties testing, and the right side of the figure is the reference color of the crystal orientation. If it is a single crystal, a and b are one color, and if it is a polycrystalline, a and b are multiple colors. Figure 6 It can be seen that the molybdenum single crystal rod obtained in Comparative Example 1 undergoes recrystallization after thermal deformation, while the molybdenum-niobium alloy single crystal rod obtained in Example 2 still maintains a single crystal structure after thermal deformation.
[0054] It was tested that the compressive strength of the molybdenum-niobium alloy single crystal rod obtained in Example 2 was 252.39 MPa, and the single crystal structure was maintained after thermal deformation, while the compressive strength of the molybdenum single crystal rod obtained in Comparative Example 1 was 102.8 MPa, and recrystallization occurred after thermal deformation.
[0055] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for improving the high temperature mechanical properties of molybdenum single crystals and maintaining the stability of the single crystal structure, characterized in that: The method comprises the following steps: Step 1: preparing a molybdenum-niobium alloy sintered bar by powder metallurgy; Step 2: melting, extruding, forging and machining the molybdenum-niobium alloy sintered bar prepared in step 1 in sequence to obtain a molybdenum-niobium alloy raw material bar; Step 3: Electron beam zone melting the molybdenum-niobium alloy raw material rod obtained in step 2 to obtain a molybdenum-niobium alloy single crystal rod; Step 4: Prepare the molybdenum-niobium alloy single crystal rod obtained in step 3 as a sample, and then conduct high-temperature mechanical property test and structural analysis in sequence to determine its high-temperature mechanical properties and single crystal structural stability.
2. A method for improving the high temperature mechanical properties of molybdenum single crystal and maintaining the stability of the single crystal structure according to claim 1, characterized in that: The smelting in step 2 is electron beam suspension zone melting.
3. A method for improving high temperature mechanical properties of molybdenum single crystal and maintaining single crystal structural stability according to claim 1, characterized in that: The mass percentage of niobium in the molybdenum-niobium alloy single crystal rod in step 4 is 3% to 6%, and the balance is molybdenum.
4. A method for improving high temperature mechanical properties of molybdenum single crystal and maintaining single crystal structural stability according to claim 1, characterized in that: The preparation of the sample in step 4 is specifically as follows: a cylindrical compression sample with a diameter of 6 mm and a length of 9 mm is cut out from the molybdenum-niobium alloy single crystal rod by wire cutting.
5. The method for improving the high temperature mechanical properties of molybdenum single crystal and maintaining the stability of the single crystal structure according to claim 1, characterized in that: The equipment used for the high temperature mechanical properties test in step 4 is a Gleeble-1500D thermal simulation tester. The temperature used for the high temperature mechanical properties test is 1100°C to 1400°C, and the strain rate is 10 -2 s -1 , the deformation is 50%.
6. A method for improving high temperature mechanical properties of molybdenum single crystal and maintaining single crystal structural stability according to claim 1, characterized in that: The structural analysis described in step 4 is a single crystal structural analysis, specifically using electron backscatter diffraction to determine the crystal orientation of the single crystal sample.
